Perspektif Hukum Persaingan Usaha Terhadap Kebijakan Demonopolisasi Badan Usaha Milik Negara di Indonesia - Putu Samawati (Simbur Cahaya, 2018)
Business competition law requires the creation of national economic efficiency and the effectiveness and efficiency of business activities as contained in the purpose of the establishment of Law No.5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. The effectiveness and efficiency of business activities are directed at creating healthy competition between business actors. While national economic efficiency is directed at fulfilling the needs of the lives of many people with indicators of increasing public welfare. One of the efforts to achieve these two things was done by enacting the de-monopolization policy of State-Owned Enterprises (BUMN), in which state-owned companies that had monopoly rights in certain business sectors, their monopoly rights were revoked by giving opportunities to the private sector to compete. The study of how the de-monopolization policy of SOEs can create a healthy business competition climate for the fulfillment of the needs of the people's lives is the focus of the discussion in this article. The discussion will be conducted using the documentary research method that places secondary data as the main analysis material. Analysis using a legislative approach, and a historical approach will be able to answer the problems that use the principle of benefit and principle of justice that can be used as a government consideration in enforcing the de-monopolization policy of SOEs. The main target of the de-monopolization policy of SOEs is to protect the lives of many people by guaranteeing the fulfillment of quality living needs